13=1/6y+2x
-1/6y -1/6y
-1/6y+13=2x
-13 -13
-1/6y=2x-13
*-6 *-6
y=-12x-13
*I multiply it by -6 because -6 is the reciprocal of -1/6, and I can't divide -1/6, actually I can, but it just going to be more confusing that way, and the fastest way to get rid of the -1/6 when you solving this type of equation is multiply it by its reciprocal.
Answer:
to solve use the distributive property and multiply
Step-by-step explanation:
I'm sorry I do not have the product
Answer: 17/3
Step-by-step explanation:
I believe the answers for this is D